Modern credit management : a study of the management of trade credit under inflationary conditions - Kirkman, Patrick R. A. (London : Allen & Unwin, 1977)
This book has been produced to discuss cash management policy, credit policy and organization. In Europe there are a large number of different credit practices, although settlement in under sixty days is quite usual in many countries.
Includes bibliographical references and index.
occ 17/01/2019
Loans
Keywords: Credit management